EFFECT OF ENTREPRENEURSHIP ORIENTATION AND MARKET ORIENTATION ON MARKETING PERFORMANCE THROUGH COMPETITIVE ADVANTAGE - Fatikha, Cindera; Rahayu, Mintarti; Sumiati, Sumiati (Universitas Brawijaya, Indonesia, 2021)
This study aims to analyze the effect of entrepreneurial orientation, market orientation, and competitive advantage on marketing performance; test the effect entrepreneurial orientation and market orientation towards marketing performance are mediated by competitive advantage. The sample in this study was 132 owners from a population of 463 SMEs owners of Tempe chips. The sampling technique in this study used purposive sampling. Data analysis techniques using Partial Least Squares (PLS). The results showed that entrepreneurial orientation had a direct positive effect on marketing performance; market orientation has a direct positive effect on marketing performance; entrepreneurial orientation has a direct positive effect on competitive advantage; market orientation has a direct positive effect on competitive advantage; competitive advantage has a direct positive effect on marketing performance; entrepreneurial orientation has a positive effect on marketing performance through competitive advantage; Market orientation has a positive effect on marketing performance through competitive advantage. Competitive advantage acts as a partial mediating variable.